Co-Amorphous Solid Dispersions for Solubility and Absorption Improvement of Drugs: Composition, Preparation, Characterization and Formulations for Oral Delivery - Anna Karagianni; Kyriakos Kachrimanis; Ioannis Nikolakakis (MDPI AG, 2018)
The amorphous solid state offers an improved apparent solubility and dissolution rate. However, due to thermodynamic instability and recrystallization tendencies during processing, storage and dissolution, their potential application is limited. For this reason, the production of amorphous drugs with adequate stability remains a major challenge and formulation strategies based on solid molecular dispersions are being exploited. Co-amorphous systems are a new formulation approach where the amorphous drug is stabilized through strong intermolecular interactions by a low molecular co-former. This review covers several topics applicable to co-amorphous drug delivery systems. In particular, it describes recent advances in the co-amorphous composition, preparation and solid-state characterization, as well as improvements of dissolution performance and absorption are detailed. Examples of drug-drug, drug-carboxylic acid and drug-amino acid co-amorphous dispersions interacting via hydrogen bonding, π−π interactions and ionic forces, are presented together with corresponding final dosage forms.